Method for producing a zirconia dental article
By coloring and glazing dental zirconia products in their gel state, the problems of insufficient aesthetics and durability in existing technologies are solved, enabling customized production without additional modification steps and obtaining smooth and glossy dental zirconia products.
Patent Information
- Application Number
- CN202480028363.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-10
- Filing Date
- 2024-04-11
- Publication Date
- 2026-01-06
AI Technical Summary
Existing technologies struggle to produce dental zirconia products that are both aesthetically pleasing and durable, and the customization process requires additional modification steps such as milling.
A zirconia gel product is constructed using a radiation-curable zirconia sol in a laminated manufacturing method. The product is then colored and glazed in the gel state, subsequently transformed into a zirconia aerogel product, and finally sintered to obtain a smooth and glossy surface.
It enables the production of custom dental products without additional modification steps, featuring high durability and a glossy surface, reduced risk of wear, and improved aesthetics and processing efficiency.
Smart Images

Figure CN121285362A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing dental zirconia articles, a dental zirconia article obtainable by such method, and a kit comprising two different zirconia sols to be processed in such method. Background Technology
[0002] It is well known that ceramic sols are processed using a layered manufacturing technique.
[0003] US 2015 / 0223917 A1 (Herrmann et al.) relates to a kit comprising: a coloring solution; a porous zirconia article; optional application equipment; wherein the coloring solution contains: a solvent of cations and ions of a colorant in an amount greater than about 0.05 mol per part of the coloring solution; optional complexing agent; optional thickener; optional organic labeling substance; and optional additives; wherein the porous zirconia article exhibits N2 adsorption and desorption according to the IUPAC type IV isotherm and about 10 m 2 / g to approximately 200m 2 / g of BET surface.
[0004] WO 01 / 13815 A1 (Feenstra) describes a method for manufacturing dental components using 3D printing technology. Nanomaterials consisting of nano-inorganic solid particles having polymerizable organic groups on their surface are preferably used as the curable material. Following the printing process, the dental components typically undergo a post-heating treatment between 60°C and 150°C to complete curing. Alternatively or supplemented, thermal densification is achieved, wherein the dental components are heated to a temperature of at least 250°C.
[0005] US 10,759,707 (Mayr et al.) discloses a method for producing ceramic articles, the method comprising the steps of: providing a printing sol comprising a solvent, nanoscale particles, a radiation-curable monomer, and a photoinitiator, the printing sol having a viscosity of less than 500 mPa*s at 23°C; processing the printing sol as a building material in a laminated manufacturing method to obtain a 3D article in a gel state having a volume A; converting the 3D article in the gel state into a 3D article in an aerogel state; and heat-treating the 3D article to obtain a sintered 3D ceramic article having a volume F, wherein the volume A of the 3D article in the gel state is greater than 500% of the volume F of the sintered ceramic article. Ceramic articles obtainable according to this method are also described, which may have the shape of dental or orthodontic articles.
[0006] US 2021 / 32283 A1 (Jans et al.) describes a glazing composition suitable for glazing the surface of dental zirconia articles. The glazing composition comprises a liquid, glass particles, and hydrophilic silica nanoparticles. Summary of the Invention
[0007] However, a method for producing highly aesthetically pleasing dental zirconia products is still needed.
[0008] This method should allow for the production of custom dental products that can be used by physicians without further modification steps such as milling.
[0009] Ideally, custom-made dental products should have a glossy surface.
[0010] In one aspect, the present invention is characterized by a method for producing dental zirconia articles, the method comprising the following steps:
[0011] (a) A radiation-curable zirconia sol A, used as a structural material, is processed in a laminated manufacturing method including a radiation curing step to obtain a zirconia gel article having the shape of a dental article with an outer surface and an inner surface.
[0012] (b) Radiation-curable zirconia sol B x Applied to at least a portion of the outer surface of the zirconia gel article.
[0013] (c) Radiation-curable zirconia sol B in step (b) x ,
[0014] (d) Convert the zirconia gel product into a zirconia aerogel product.
[0015] As claimed and described herein, the radiation-curable zirconia sol A is similar to the radiation-curable zirconia sol B in terms of chemical composition and / or physical properties. x Same or different.
[0016] In another respect, the present invention relates to dental zirconia articles that are obtainable or acquireable by means of the claims and the methods described herein.
[0017] Unless otherwise defined, the following terms shall have the given meaning for the purposes of this specification:
[0018] "Cureable, curable, or polymerizable component" is any component that can be cured or solidified by radiation-induced polymerization in the presence of a photoinitiator. A cureable component may contain only one, two, three, or more polymerizable groups. Typical examples of polymerizable groups include unsaturated carbon groups, such as vinyl groups, which are particularly present in (meth)acrylate groups.
[0019] As used herein, “(meth)acryloyl” is an abbreviation for “acryloyl” and / or “methacryloyl”. For example, “(meth)acryloyloxy” is an abbreviation for an acryloyloxy group (i.e., CH2=CH-C(O)-O-) and / or a methacryloyloxy group (i.e., CH2=C(CH3)-C(O)-O-).
[0020] As used herein, the terms "hardening" and "curing" are used interchangeably and refer to polymerization and / or crosslinking reactions involving one or more materials contained in the composition, including, for example, photopolymerization and chemical polymerization techniques (e.g., ionic or chemical reactions that form free radicals that effectively polymerize olefinic unsaturated compounds).
[0021] "Dental articles" refers to articles intended for use in the dental or orthodontic field, particularly as or for the manufacture of dental restorations. Dental articles typically have two distinct surface parts: an outer surface and an inner surface. The outer surface is the surface that is not normally in permanent contact with the tooth surface. Conversely, the inner surface is the surface used to attach or fix the dental article to the tooth. If the dental article has the shape of a crown or inlay, the inner surface is usually concave, while the outer surface is usually convex. Dental articles should not contain components harmful to patient health and therefore should not contain hazardous or toxic components that could migrate from dental or orthodontic articles.
[0022] "Dental restorations" refers to dental products used to restore teeth that are in need of treatment. Examples of dental restorations include crowns, bridges, inlays, high inlays, veneers, and their components.
[0023] Examples of orthodontic products include brackets, buccal tubes, splints, and buttons, as well as their components.
[0024] A "sol" is a continuous liquid phase containing discrete particles ranging in size from 1 nm to 100 nm or 1 nm to 50 nm, also known as a "colloidal solution." The sols described in this paper are translucent and do exhibit the so-called "Tyndall effect" or "Tyndall scattering." The particle size is below the wavelength of visible light (400 nm to 700 nm).
[0025] "Coloring ion" should mean an ion that has absorption in the visible spectrum (e.g., from about 380 nm to about 780 nm), which produces a colored solution (visible to the human eye) if the coloring ion is dissolved in water (e.g., about 0.6 mol / L) and / or causes a coloring effect in zirconia articles containing the coloring ion.
[0026] A composition can be characterized as "transparent" if the visible light beam (380 nm to 780 nm) is not scattered by the composition and cannot be observed by side viewing (i.e., there is no Tyndall effect). However, the intensity of the visible light penetrating the beam in the beam direction may be reduced due to the absorption of light by the coloring ions. Transparent compositions allow light to pass through according to Snell's law (the classical law of refraction). Therefore, details of an image are visible through a thin sheet of transparent material.
[0027] A translucent composition allows light to pass through partially, although it is not completely transparent, exhibiting significant volume scattering of transmitted light. The opposite property of translucency is opacity (O). O = 1 / T = I / I0 (T = transmittance, I = intensity of transmitted light, I0 = intensity of light before transmission). Therefore, for a 1mm thick sheet with a diameter of 15mm, an opacity value less than approximately 0.9 is considered translucent (e.g., for measurements performed using the Color i7 device from X-Rite, USA, measurement mode: reflection contrast ratio). Opacity can be measured in various ways: transmission, reflection, and reflection using a contrast ratio method.
[0028] "Particle" refers to a solid substance with a geometrically defined shape. The shape can be regular or irregular. Particles can typically be analyzed in terms of, for example, particle size and particle size distribution.
[0029] The term "primary particle size" refers to the size of an unassociated individual particle (which is considered a primary particle). X-ray diffraction (XRD) is commonly used to measure primary particle size.
[0030] If a dental ceramic article has undergone heat treatment (temperature range of 900°C to 1,100°C) for 1 to 3 hours, such that the original fracture resistance of the dental ceramic, measured according to the "Three-Ball Impact Test" ISO 6872, is in the range of 15 MPa to 55 MPa or 30 MPa to 50 MPa, then the dental ceramic article is classified as "pre-sintered". Pre-sintered dental ceramic articles typically have a porous structure and are similar to fully sintered dental ceramic frames (3 mol% yttrium-stabilized zirconia ceramic typically has a strength of 6.1 g / cm³). 3 Compared to yttrium-stabilized zirconia ceramics, its density (typically 3.0 g / cm³ for 3 mol% yttrium-stabilized zirconia ceramics) is much lower. 3 (It is relatively small.)
[0031] "Ceramic zirconia articles" should mean three-dimensional articles, wherein at least one of the x, y, and z dimensions is at least about 5 mm, and the articles contain 80% by weight or at least 90% by weight of zirconia.
[0032] "Integral ceramic zirconia products" should refer to products whose surface is not coated with materials or compositions other than zirconia.
[0033] "Ceramics" refers to inorganic non-metallic materials produced by applying heat. Ceramics are typically hard, porous, and brittle, and exhibit an essentially purely crystalline structure compared to glass or glass-ceramics.
[0034] "Crystallization" refers to a solid composed of atoms arranged in a three-dimensional periodic pattern (i.e., having a long-range crystal structure as determined by X-ray diffraction). Crystal structures include tetragonal, monoclinic, cubic zirconia, and mixtures thereof.
[0035] "Percolation" is a technique that uses ultrafiltration membranes to completely remove, replace, or reduce the concentration of salts or solvents from a solution containing organic molecules. This method selectively utilizes permeable (porous) membrane filters to separate components of solutions and suspensions based on molecular size.
[0036] The term "aerogel" should refer to a three-dimensional low-density solid (i.e., an article with a porosity of less than 0.1% by volume and a density of less than 20%). Aerogels are porous materials derived from gels in which the liquid component of the gel has been replaced by a gas. Solvent removal is typically carried out under supercritical conditions. During this process, the network essentially does not shrink, and a highly porous, low-density material can be obtained.
[0037] Density refers to the ratio of an object's mass to its volume. The unit of density is usually g / cm³. 3 The density of an object can be calculated, for example, by determining its volume (e.g., by calculating or applying Archimedes' principle or method) and measuring its mass.
[0038] The term "tubular reactor" refers to the heated portion (i.e., the heating zone) of a continuous hydrothermal reactor system. Tubular reactors can be of any suitable shape. The shape of a tubular reactor is typically chosen based on the desired length of the reactor and the method used to heat it. For example, a tubular reactor can be straight, U-shaped, or coiled. The internal portion of a tubular reactor can be hollow or may contain baffles, spheres, or other known mixing technologies.
[0039] The term "calcination" refers to a method of heating a solid material to remove at least 90% by weight of volatile chemically bound components (e.g., organic components) (as opposed to, for example, drying, where physically bound water is removed by heating). Calcination is carried out at a temperature below that required for the pre-sintering step.
[0040] The terms "sintering" and "firing" are used interchangeably. Pre-sintered ceramic articles shrink during the sintering step (i.e., if sufficient temperature is applied). The sintering temperature to be applied depends on the ceramic material chosen. For zirconia-based ceramics, typical sintering temperatures range from 1,100°C to 1,400°C. Sintering typically involves densifying porous materials into less porous materials with higher density (or fewer pores). In some cases, sintering may also involve a change in the phase composition of the material (e.g., a partial transformation of an amorphous phase into a crystalline phase).
[0041] "Layered manufacturing" refers to methods used to create 3D artifacts. An example of layered manufacturing technology is stereolithography (SLA), in which continuous layers of material are laid down under computer control. The artifacts can be of almost any shape or geometry and are produced from 3D models or other electronic data sources.
[0042] “Environmental conditions” means the conditions under which the compositions described herein are typically subjected during storage and handling. Environmental conditions can be, for example, pressures of 900 mbar to 1,100 mbar, temperatures of 10°C to 40°C, and relative humidity of 10% to 100%. In a laboratory setting, environmental conditions are typically adjusted to 20°C to 25°C and 1,000 mbar to 1,025 mbar (at sea level).
[0043] As used herein, “an,” “a,” “the,” “at least one,” and “one or more” are used interchangeably. Also in this document, numerical ranges expressed by endpoints include all numbers contained within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0044] Adding "plural form" to a term means that the term should include both singular and plural forms. For example, the term "additive" means one additive and multiple additives (e.g., 2, 3, 4, etc.).
[0045] Unless otherwise specified, all figures used in the specification and claims that indicate the quantity of components, the results of physical property measurements (such as those described below), etc., shall be understood to be modified by the term "about" in all cases.
[0046] When these terms appear in the specification and claims, the terms "comprising" or "including" and their variations are not restrictive. "Constitutes substantially of" means that specific additional components may be present, namely those components that do not substantially affect the essential properties of the article or composition. "Constitutes of" means that no additional components should be present. The term "comprising" should also include the terms "constitutes substantially of" and "composes of".
[0047] If a composition does not contain a certain component as an essential feature, then the composition is "substantially or substantially free of" said component. Therefore, the component itself is not intentionally added to the composition, nor is it intentionally added to the composition along with other components or components of other components. A composition substantially free of a certain component typically does not contain that component at all. However, sometimes the presence of a small amount of said component is unavoidable, for example, due to impurities contained in the raw materials used. Attached Figure Description
[0048] Figure 1 The illustration shows volume shrinkage that occurs when a printed gel article is converted into an aerogel article, followed by pre-sintering and full sintering (from left to right).
[0049] Figure 2 The images show dental zirconia veneers prepared according to the present invention (two samples on the right) and dental zirconia veneers not prepared according to the present invention (two samples on the left). Detailed Implementation
[0050] Several advantageous features have been found in the invention described in the text.
[0051] Compared to existing molding and / or subtractive methods (e.g., machining ceramic articles from grinding blanks), the present invention facilitates a stacked, moldless method for manufacturing the final part.
[0052] Currently, individualization of dental zirconia products is typically achieved by using enamel and / or coloring compositions that are chemically different from the underlying zirconia material, applied to the sintered dental zirconia product. Generally, glass window materials are also less durable than zirconia materials.
[0053] This can lead to undesirable aesthetic changes in the appearance of dental products over time. Furthermore, this structure can also result in increased wear on the relative teeth.
[0054] Furthermore, the individualization of the surface of sintered dental zirconia products is labor-intensive and requires specific skills and equipment due to their small size.
[0055] According to the invention, if necessary, glazing and coloring can be performed using the same zirconium oxide material used for the production of dental articles.
[0056] Because the glazing material undergoes the same processing steps as the underlying zirconia material, the resulting dental products are more durable.
[0057] Dental products obtained and inserted into the patient's mouth in this way will not show excessive wear on the opposing teeth.
[0058] The method described in this paper allows the final desired shape to be produced during the lamination manufacturing process.
[0059] The printed zirconia gel can be colored and glazed using materials that are the same as or similar to the zirconia gel itself.
[0060] This results in a high-quality glazed surface that is also highly durable and can be given different colors depending on the composition of the dopants in the coating liquid.
[0061] Surprisingly, the application of radiation-cured sol, which was already in its early stages, resulted in dental zirconia products having a smooth and glossy surface after sintering, while dental products not treated in this way had a matte surface even after cleaning.
[0062] Additionally, improper cleaning often results in a blurry white surface, but in this case, the excess sol coating will not turn white.
[0063] Furthermore, since coloring and / or glazing are performed on the surface of a dental article in a gel state, coloring and / or glazing can more easily penetrate the gel material of the dental article.
[0064] The fact that dental zirconia products in a gel state are much larger than those after sintering facilitates the individualization of the surface of dental zirconia products.
[0065] The method described herein allows the production of sol-gel bodies with a resolution of 25 μm in the z-direction and 40 µm × 40 µm (= pixel size) in the xy-direction, thereby producing ceramic bodies (after sintering) with, for example, a resolution of 12.5 µm in the z-direction and 20 µm × 20 µm in the xy-direction.
[0066] In the first step, radiation-curable zirconia sol A is processed as a building material in a laminated manufacturing method that includes a radiation curing step to obtain a zirconia gel product. Radiation-curable zirconia sol A is also known as a printing sol.
[0067] Zirconia gel products have the shape of dental products with outer and inner surfaces, that is, zirconia gel products have a 3-dimensional shape.
[0068] Radiation-curable zirconia sol A is a dispersion of crystalline zirconia particles in a liquid.
[0069] Suitable sols are typically described in, for example, WO 2013 / 055432 A1 (3M), which relates to aerogels containing zirconium oxide, calcined articles and crystalline articles thereof, and methods for their preparation. US 7,429,422 (Davidson et al.) also describes methods for preparing usable zirconium oxide-based sols. Further usable sols are described in WO 2016 / 140840A1 (3M). The above references are incorporated herein by reference.
[0070] Radiation-curable zirconia sol A contains
[0071] Crystalline zirconium oxide particles, preferably in an amount of 25% to 65% by weight.
[0072] The crystalline phase stabilizer component is preferably present in an amount of 2 mol% to 8 mol% relative to the total oxide content of the crystalline oxide particles.
[0073] The radiation-curable component is preferably present in an amount of 2% to 30% by weight.
[0074] The photoinitiator is preferably used in an amount of 0.01% to 3% by weight.
[0075] Liquid, preferably in an amount of 20% to 70% by weight.
[0076] Optional coloring ions, preferably in an amount of 0% to 2% by weight,
[0077] The optional inhibitor component is preferably in an amount of 0% to 0.5% by weight.
[0078] Weight % relative to the weight of radiation-cured zirconia sol A.
[0079] The phase stabilizer component is typically contained within the crystalline zirconia particles, and optional coloring ions can be contained within the crystalline zirconia particles and / or exist as separate components.
[0080] The crystalline zirconia particles in zirconia sol A typically have a primary particle size in the range of 2 nm to 50 nm (in some embodiments, 5 nm to 50 nm, 2 nm to 25 nm, 5 nm to 25 nm, 2 nm to 15 nm, or even 5 nm to 15 nm).
[0081] Crystalline zirconia particles are typically present in the following amounts: at least 25% by weight, or at least 30% by weight, or at least 35% by weight; up to 65% by weight, or up to 60% by weight, or up to 55% by weight; 25% to 65% by weight, or 30% to 60% by weight, or 35% to 55% by weight; by weight relative to the weight of the printing sol.
[0082] The crystalline phase stabilizing components that can be used include Ce, Mg, Ca, Y, La, oxides of rare earth elements, and combinations thereof, with Y and La sometimes being preferred.
[0083] The phase stabilizer component, calculated as oxide, is typically present in the following amounts: at least 2 mol%, or at least 3 mol%, or at least 4 mol%; up to 8 mol%, or up to 7 mol%, or up to 6 mol%; 2 mol% to 8 mol%, or 3 mol% to 7 mol%, or 4 mol% to 6 mol%; mol% relative to total crystalline oxide particles.
[0084] The radiation-curable components present in the printing sol can be described as a first monomer, a second monomer, a third monomer, etc.
[0085] If desired, the zirconia particles that have been surface-modified with a polymerizable agent can be polymerized to provide a composition comprising cross-linked zirconia particles.
[0086] The first monomer can be used as a polymerizable surface modifier. A variety of first monomers can be used.
[0087] The surface modifier can be represented by formula AB, wherein the A group can be attached to the surface of the zirconium oxide-based particles, and the B group is radiation-curable.
[0088] Group A can be attached to the surface of zirconium-based particles by adsorption, forming ionic bonds, forming covalent bonds, or a combination thereof.
[0089] Examples of group A include acidic moieties (such as carboxylic acid groups, phosphate groups, sulfonic acid groups and their anions) and silanes.
[0090] Group B contains a radiation-curable portion.
[0091] Examples of group B include vinyl groups, particularly acryloyl or methacryloyl moieties.
[0092] Suitable surface modifiers include polymerizable carboxylic acids and / or their anions, polymerizable sulfonic acids and / or their anions, polymerizable phosphoric acids and / or their anions, and polymerizable silanes. Suitable surface modifiers are further described, for example, in WO2009 / 085926 A1 (Kolb et al.).
[0093] Examples of free radical polymerizable surface modifiers are polymerizable surface modifiers containing an acidic moiety or its anion (e.g., a carboxylic acid group).
[0094] Exemplary acid-free radical polymerizable surface modifiers include acrylic acid, methacrylic acid, β-carboxyethyl acrylate, and mono-2-(methacryloyloxyethyl) succinate.
[0095] Exemplary free-radical polymerizable surface modifiers can be the reaction products of hydroxyl-containing polymerizable monomers and cyclic acid anhydrides (such as succinic anhydride, maleic anhydride, and phthalic anhydride). Exemplary polymerizable hydroxyl-containing monomers include hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, and hydroxybutyl methacrylate. Acryloyloxy and methacryloxy-functionalized polyethylene oxides and polypropylene oxides can also be used as polymerizable hydroxyl-containing monomers.
[0096] An exemplary free radical polymerizable surface modifier for imparting both polarity and reactivity to zirconium oxide-containing nanoparticles is succinate mono(methacryloyloxy polyethylene glycol).
[0097] Another example of a surface modifier that can be polymerized by free radicals is a polymerizable silane.
[0098] Exemplary polymerizable silanes include methacryloyloxyalkyltrialkoxysilanes or acryloyloxyalkyltrialkoxysilanes (e.g., 3-methacryloyloxypropyltrimethoxysilane, 3-acryloyloxypropyltrimethoxysilane, and 3-(methacryloyloxy)propyltriethoxysilane); methacryloyloxyalkylalkyldialkoxysilanes or acryloyloxyalkylalkyldialkoxysilanes (e.g., 3-(methacryloyloxy)propylmethyldimethoxysilane and 3-(acryloyloxypropyl)methyldimethoxysilane); methacryloyloxyalkyldialkylalkoxysilanes or acryloyl... alkyl-dialkylalkoxysilanes (e.g., 3-(methacryloyloxy)propyldimethylethoxysilane); mercaptoalkyltrialkoxysilanes (e.g., 3-mercaptopropyltrimethoxysilane); aryltrialkoxysilanes (e.g., styrylethyltrimethoxysilane); vinylsilanes (e.g., vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, and vinyltri(2-methoxyethoxy)silane).
[0099] According to one embodiment, the printing sol described herein comprises one or more second monomers, which contain at least two radiation-curable portions. These second monomers may act as crosslinking agents during the gel formation step.
[0100] Any suitable second monomer that does not have surface-modifying groups can be used. That is, the optional second monomer does not have carboxylic acid groups or silyl groups. The second monomer is typically a polar monomer (e.g., a non-acidic polar monomer), a monomer having multiple polymerizable groups, an alkyl (meth)acrylate, or a mixture thereof.
[0101] The presence of monomers with multiple polymerizable groups tends to enhance the strength of the gel composition formed during sol-gel polymerization.
[0102] The number of polymerizable groups can range from 2 to 6 or even higher. In many embodiments, the number of polymerizable groups ranges from 2 to 5 or 2 to 4. The polymerizable groups are typically (meth)acryloyl groups.
[0103] Exemplary monomers having two (meth)acryloyl groups include 1,2-ethylene glycol diacrylate, 1,3-propanediol diacrylate, 1,9-nonanediol diacrylate, 1,12-dodecanediol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, butanediol diacrylate, bisphenol A diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, polyethylene / polypropylene copolymer diacrylate, polybutadiene di(meth)acrylate, propoxylated glycerol tri(meth)acrylate, and caprolactone modified with neopentyl glycol hydroxyneoplastate diacrylate.
[0104] Exemplary monomers having three or four (meth)acryloyl groups include trimethylolpropane triacrylate (e.g., available under the trade name TMPTA-N from Cytec Industries, Inc. (Smyrna, GA, USA) and under the trade name SR-351 from Sartomer (Exton, PA, USA), pentaerythritol triacrylate (e.g., available under the trade name SR-444 from Sartomer), ethoxylated (3)trimethylolpropane triacrylate (e.g., available under the trade name SR-454 from Sartomer), ethoxylated (4)pentaerythritol tetraacrylate (e.g., available under the trade name SR-494 from Sartomer), tris(2-hydroxyethyl isocyanurate) triacrylate (e.g., available under the trade name SR-368 from Sartomer), and mixtures of pentaerythritol triacrylate and pentaerythritol tetraacrylate (e.g., available under the trade name PETIA from Cytec Industries, Inc.). Available from Inc., wherein the ratio of tetraacrylate to triacrylate is approximately 1:1, and available under the trade name PETA-K, wherein the ratio of tetraacrylate to triacrylate is approximately 3:1; pentaerythritol tetraacrylate (e.g., available from Sartomer under the trade name SR-295); and di-trimethylolpropane tetraacrylate (e.g., available from Sartomer under the trade name SR-355).
[0105] Exemplary monomers having five or six (meth)acryloyl groups include dipentaerythritol pentaacrylate (e.g., available commercially from Sartomer under the trade name SR-399) and hexafunctional polyurethane acrylate (e.g., available commercially from Sartomer under the trade name CN975).
[0106] In some embodiments, the optional second monomer is a polar monomer. As used herein, the term "polar monomer" refers to a monomer having a free radical polymerizable group and a polar group. The polar group is typically non-acidic and typically contains a hydroxyl group, a primary amide group, a secondary amide group, a tertiary amide group, an amino group, or an ether group (i.e., a group containing at least one alkylene-oxy-alkylene group of the formula -ROR-, wherein each R is an alkylene having 1 to 4 carbon atoms).
[0107] Suitable optional polar monomers having hydroxyl groups include, but are not limited to, hydroxyalkyl methacrylates (e.g., 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, and 4-hydroxybutyl methacrylate) and hydroxyalkyl (meth)acrylamides (e.g., 2-hydroxyethyl (meth)acrylamides or 3-hydroxypropyl (meth)acrylamides), ethoxylated hydroxyethyl (meth)acrylates (e.g., monomers commercially available from Sartomer (Exton, PA, USA) under the trade names CD570, CD571, and CD572), and aryloxy-substituted hydroxyalkyl (meth)acrylates (e.g., 2-hydroxy-2-phenoxy-propyl (meth)acrylate).
[0108] Exemplary polar monomers having a primary amide group include (meth)acrylamide. Exemplary polar monomers having a secondary amide group include, but are not limited to, N-alkyl (meth)acrylamides, such as N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-tert-octyl (meth)acrylamide, and N-octyl (meth)acrylamide. Exemplary polar monomers having a tert-amide group include, but are not limited to, N-vinylcaprolactam, N-vinyl-2-pyrrolidone, (meth)acryloylmorpholine, and N,N-dialkyl (meth)acrylamides, such as N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, and N,N-dibutyl (meth)acrylamide.
[0109] Polar monomers having an amino group include various N,N-dialkylaminoalkyl esters and N,N-dialkylaminoalkyl (meth)acrylamides. Examples include, but are not limited to, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, N,N-diethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylamide, N,N-diethylaminopropyl (meth)acrylamide, and N,N-diethylaminopropyl (meth)acrylamide.
[0110] Exemplary polar monomers having ether groups include, but are not limited to, alkoxylated alkyl (meth)acrylates such as ethoxyethoxyethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, and 2-ethoxyethyl (meth)acrylate; and poly(epoxyalkylene)(meth)acrylates such as poly(ethylene oxide)(meth)acrylate and poly(propylene oxide)(meth)acrylate. Poly(epoxyalkylene)acrylates are commonly referred to as poly(alkylene glycol)(meth)acrylates. These monomers may have any suitable end groups, such as hydroxyl or alkoxy groups. For example, when the end group is a methoxy group, the monomer may be referred to as methoxy poly(ethylene glycol)(meth)acrylate.
[0111] Suitable alkyl (meth)acrylates that can be used as a second monomer may have alkyl groups having a straight-chain, branched, or cyclic structure. Examples of suitable alkyl (meth)acrylates include, but are not limited to, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, 2-methylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-methyl-2-pentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-methylhexyl (meth)acrylate, n-octyl (meth)acrylate, and (meth)acrylate. Isooctyl acrylate, 2-octyl acrylate, isononyl acrylate, isoamyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, n-decyl acrylate, isodecyl acrylate, isobornyl acrylate, 2-propylheptyl acrylate, isotridecyl acrylate, isostearyl acrylate, octadecyl acrylate, 2-octyldecyl acrylate, dodecyl acrylate, lauryl acrylate, and heptadecanyl acrylate.
[0112] In some implementations, the second monomer can be characterized by the following characteristics, either individually or in combination:
[0113] It is soluble in the liquid contained in the sol;
[0114] It has at least one, two, or three radiation-cured components;
[0115] Radiation-curable portion having a portion selected from vinyl, acryloyl, or methacryloyl groups;
[0116] Molecular weight: 70 g / mol to 5,000 g / mol; or 70 g / mol to 1,000 g / mol; or 100 g / mol to 500 g / mol.
[0117] Using radiation-curable components with molecular weights within the aforementioned range, as described above, is advantageous for providing sols with the desired viscosity. Lower molecular weight components are generally also better soluble than higher molecular weight components.
[0118] Radiation-curable components are typically present in the following amounts: at least 2% by weight, or at least 5% by weight, or at least 10% by weight; up to 30% by weight, or up to 25% by weight, or up to 20% by weight; 2% to 30% by weight, or 5% to 25% by weight, or 10% to 20% by weight; by weight relative to the weight of the printing sol.
[0119] The printing sol described herein contains one or more photoinitiators.
[0120] There are no particular restrictions on the properties and structure of photoinitiators, unless the desired results cannot be achieved.
[0121] In some embodiments, the photoinitiator can be characterized by the following characteristics, alone or in combination: soluble in the liquid contained in the sol; radiation absorption in the range of 200 nm to 500 nm or 300 nm to 450 nm.
[0122] The photoinitiator should be able to initiate or trigger the curing or hardening reaction of the radiation-curable components present in the printing sol.
[0123] In some implementations, the following categories of photoinitiators may be used: a) two-component systems in which radicals are generated by abstracting hydrogen atoms from a donor compound; b) one-component systems in which two radicals are generated by cleavage.
[0124] Examples of photoinitiators of type (a) typically contain a moiety selected from benzophenone, xanthonone, or quinone in combination with an aliphatic amine.
[0125] Examples of photoinitiators of type (b) typically contain a moiety selected from benzoyl ether, acetophenone, benzoyl oxime, or acylphosphine.
[0126] Exemplary UV initiators include 1-hydroxycyclohexylbenzophenone (available under the trade name “IRGACURE 184” (formerly from Ciba Specialty Chemicals Corp., Tarrytown, NY)), 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)methyl ketone (available under the trade name “IRGACURE 2529” (formerly from Ciba Specialty Chemicals Corp.)), 2-hydroxy-2-methylphenylacetone (available under the trade name “DAROCURE D111” (formerly from Ciba Specialty Chemicals Corp.)), and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (available under the trade name “IRGACURE 819” (formerly from Ciba Specialty Chemicals Corp.)).
[0127] The photoinitiator is typically present in the following amounts: at least 0.01% by weight, or at least 0.05% by weight, or at least 0.08% by weight; at most 3% by weight, or at most 2% by weight, or at most 1% by weight; from 0.01% by weight to 3% by weight, or from 0.05% by weight to 2% by weight, or from 0.08% by weight to 1% by weight; by weight relative to the weight of the printing sol.
[0128] There are no particular limitations on the properties and structure of the liquid, unless the desired results cannot be achieved. In some embodiments, the solvent can be characterized by the following characteristics, alone or in combination:
[0129] a) Boiling point: above 100℃, or above 120℃, or above 150℃;
[0130] b) Molecular weight: 25 g / mol to 300 g / mol;
[0131] c) Viscosity: 0.2 mPa*s to 10 mPa*s (23°C);
[0132] d) Miscible with water;
[0133] e) Soluble in supercritical carbon dioxide or liquid carbon dioxide.
[0134] The following combinations of features are sometimes preferred: a) and b), or a), b) and c), or a), b), c) and d).
[0135] Using liquids with boiling points above 100°C or 150°C can be advantageous in reducing liquid evaporation during the process.
[0136] Using a liquid with a molecular weight and / or viscosity within the above range can be beneficial, as it helps to adjust the viscosity of the printing sol. Molecular weight can also affect the diffusion constant and how easily the liquid can be removed.
[0137] Using mixtures of different liquids can be beneficial because it allows for adjusting viscosity or post-processing properties, such as removing excess sol after printing.
[0138] During the further processing steps required to produce ceramic products, the liquid should also be easily removed.
[0139] Furthermore, the liquid should not hinder or negatively affect the polymerization of radiation-curable components present in the sol.
[0140] In this regard, it may be beneficial to use liquids that do not contain polymerizable components.
[0141] To enhance the solubility or properties of a liquid, it typically contains one or more polar moieties, including ether, alcohol, or carboxyl groups.
[0142] According to one embodiment, the liquid is typically a glycol or polyglycol, a monoether glycol or a monoether polyglycol, a diether glycol or a diether polyglycol, an ether ester glycol or an ether ester polyglycol, a carbonate, an amide or a sulfoxide (e.g., dimethyl sulfoxide).
[0143] Suitable diols or polydiols, monoether diols or monoether polydiols, diether diols or diether polydiols, and ether ester diols or ether ester polydiols generally have the following formula (I).
[0144] R 1 O-(R 2 O) n -R 1 (I)
[0145] In equation (I), each R 1 Independently, it is hydrogen, alkyl, aryl, or acyl. Suitable alkyl groups typically have 1 to 10, 1 to 6, or 1 to 4 carbon atoms. Suitable aryl groups typically have 6 to 10 carbon atoms and are usually phenyl or phenyl substituted with an alkyl group having 1 to 4 carbon atoms. Suitable acyl groups typically have the formula -(CO)R. a , where R a It is an alkyl group having 1 to 10 carbon atoms, 1 to 6 carbon atoms, 1 to 4 carbon atoms, 2 carbon atoms, or 1 carbon atom. The acyl group is usually an acetyl group (–(CO)CH3). In formula (I), each R 2 Typically, it is ethylene or propylene. The variable n is at least 1 and can be in the range of 1 to 10, 1 to 6, 1 to 4, or 1 to 3.
[0146] The diol or polydiol of formula (I) has two Rs equal to hydrogen atoms. 1 Group. Examples of diols include, but are not limited to, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, and tripropylene glycol.
[0147] The monoether diol or monoether polydiol of formula (I) has a first R equal to that of hydrogen. 1 The group and the second R equal to alkyl or aryl 1 Group. Examples of monoether diols or monoether polydiols include, but are not limited to, ethylene glycol monohexyl ether, ethylene glycol monophenyl ether, propylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monohexyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, tripropylene glycol monomethyl ether, and tripropylene glycol monobutyl ether.
[0148] The diether diol or diether polydiol of formula (I) has two R groups equal to alkyl or aryl groups. 1 Group. Examples of diether diols or diether polydiols include, but are not limited to, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, dipropylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and pentaethylene glycol dimethyl ether.
[0149] The ether ester diol or ether ester polydiol of formula (I) has a first R equal to alkyl or aryl. 1 The second R group equal to the acyl group 1 Group. Examples of ether ester diols or ether ester polydiols include, but are not limited to, ethylene glycol butyl ether acetate, diethylene glycol butyl ether acetate, and diethylene glycol ethyl ether acetate.
[0150] Other suitable organic solvents are carbonates of formula (II).
[0151] (II)
[0152] In equation (II), R 3 It is hydrogen or an alkyl group, such as an alkyl group having 1 to 4 carbon atoms, 1 to 3 carbon atoms, or 1 carbon atom. Examples include ethylene carbonate and propylene carbonate.
[0153] Other suitable organic solvents are amides of formula (III).
[0154] (III)
[0155] In formula (III), group R 4 It is hydrogen, alkyl, or related to R 5 The combination forms a quinary ring, which includes elements attached to R. 4 carbonyl groups and attached to R5 The nitrogen atom. Group R 5 It is hydrogen, alkyl, or related to R 4 The combination forms a quinary ring, which includes elements attached to R. 4 carbonyl groups and attached to R 5 The nitrogen atom. Group R 6 It is hydrogen or alkyl. Used for R 4 R 5 and R 6 Suitable alkyl groups have 1 to 6 carbon atoms, 1 to 4 carbon atoms, 1 to 3 carbon atoms, or 1 carbon atom. Examples of amide organic solvents of formula (III) include, but are not limited to, formamide, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methyl-2-pyrrolidone, and N-ethyl-2-pyrrolidone.
[0156] Specific examples of solvents that can be used include monohydric alcohols (e.g., C2 to C8 alcohols, including primary, secondary, and tertiary alcohols), polyhydric alcohols (e.g., ethylene glycol, propylene glycol, glycerol), and diethylene glycol ethyl ether (Carbitol). ™ ), 1-methoxy-2-propanol, N-methylpyrrolidone, acetonitrile, chlorobenzene, 1,4-dioxane, ethyl acetate, methyl ethyl ketone, tetrahydrofuran, toluene, xylene, and mixtures thereof.
[0157] The following solvents are sometimes preferred: ethanol, 1-methoxy-2-propanol, N-methylpyrrolidone, diethylene glycol ethyl ether, and mixtures thereof. In some cases, suitable solvents may also include low-boiling alcohols (below 100°C; such as methanol, ethanol, propanol), and mixtures thereof, or preferably the same solvents described above.
[0158] Liquids are typically present in the following amounts: at least 20% by weight, or at least 25% by weight, or at least 30% by weight; up to 70% by weight, or up to 65% by weight, or up to 60% by weight; 20% to 70% by weight, or 25% to 65% by weight, or 30% to 60% by weight.
[0159] Weight % relative to the weight of the printing sol.
[0160] Permissible coloring components particularly include those containing ions of Fe, Mn, Er, Pr, Tb, Nd, Cr, Co, and Mo. If present, these components are typically found as oxides in the sintered product.
[0161] Coloring ions are typically present in the following amounts: 0% by weight, or at least 0.01% by weight or at least 0.02% by weight; up to 2% by weight, or up to 1% by weight or up to 0.8% by weight; 0% to 2% by weight, or 0.01% to 1% by weight or 0.02% to 0.8% by weight; total coloring ions by weight relative to the weight of the printing sol.
[0162] The coloring component can be added to the printing sol as a separate component, and / or can be part of the crystalline zirconia particles.
[0163] According to another embodiment, the printing sol described in this text contains one or more inhibitors.
[0164] There are no particular restrictions on the nature and structure of inhibitors, unless the desired results cannot be achieved.
[0165] Inhibitors can extend the shelf life of printing sols, help prevent unwanted side reactions, and regulate the polymerization process of radiation-curable components present in the sol.
[0166] Adding one or more inhibitors to the printing sol can further help improve the precision or detail resolution of the ceramic surface.
[0167] In particular, it has been found that adding inhibitors to the printing sol described in this text can help improve the resolution and accuracy of the SLA process, as well as increase the shelf life of the printing sol, by reducing or avoiding undesirable scattering effects.
[0168] The inhibitor should be soluble in the solvent contained in the sol. Usable inhibitors typically contain a phenolic moiety.
[0169] Specific examples of inhibitors that may be used include: butylated hydroxytoluene (Ionol), p-methoxyphenol (MOP), hydroquinone monomethyl ether (MEHQ), 2,6-di-tert-butyl-4-methylphenol (BHT), phenothiazine, 2,2,6,6-tetramethylpiperidine-1-oxy radical (TEMPO), and mixtures thereof.
[0170] Inhibitors are typically present in the following amounts: 0% by weight, or at least 0.001% by weight or at least 0.01% by weight; up to 0.5% by weight, or up to 0.2% by weight or up to 0.15% by weight; 0% by weight to 0.5% by weight, or 0.001% by weight to 0.2% by weight or 0.01% by weight to 0.15% by weight; by weight relative to the weight of the printing sol.
[0171] Regarding its physical properties, radiation-curable zirconia sol A can be characterized by the following characteristics, either individually or in combination:
[0172] Viscosity: less than 500 mPa*s at 23°C;
[0173] For a path length of 10 mm, it is semi-transparent in the wavelength range of 420 nm to 600 nm;
[0174] For a path length of 10 mm, at a wavelength of 420 nm, it exhibits at least 5% transmittance.
[0175] pH value: 1 to 6.
[0176] The use of translucent printing sols has been found to improve the surface precision or detail resolution of ceramic products. Translucent printing sols exhibit less light scattering, which is used to polymerize the radiation-curable components contained within the sol. Increased translucency allows for a shallower curing gradient, which also allows for more uniform curing throughout the structure, as curing with translucent materials requires a lower energy dose.
[0177] Printing sols with viscosities within the aforementioned range are advantageous, for example, because they can be easily processed through fine nozzles and tubes. There is no need to heat the nozzles or tubes of the manufacturing unit or the manufacturing material itself. Low-viscosity sols self-level quickly on surfaces. Low-viscosity sols also allow for the easy removal of excess material from internal channels or deep grooves, such as in the case of narrow grooves on orthodontic brackets. Higher viscosity sols combined with lower mechanical strength green bodies make it quite difficult to achieve small resolutions in channels and recesses.
[0178] Printing sols typically have a Newtonian or near-Newtonian viscosity. That is, the viscosity is independent of the shear rate or depends only slightly on the shear rate.
[0179] The printing sol described in this article can be obtained as follows:
[0180] Provides a starting sol containing nanoscale particles.
[0181] The precursor solution is typically prepared by combining a zirconium salt (e.g., acetate) solution with a solvent (e.g., water). A phase stabilizer (e.g., yttrium acetate) is added and dissolved in the precursor solution. Optionally, a coloring component (e.g., ferric acetate) is also added to the precursor solution. The resulting composition is pumped through, for example, a hydrothermal reactor.
[0182] When subjected to hydrothermal treatment, various dissolved salts undergo hydrolysis and condensation reactions to form zirconium oxide-based particles. These reactions are often accompanied by the release of acidic byproducts, such as acetic acid.
[0183] Suitable hydrothermal reactors are described, for example, in US 5,453,262 (Dawson et al.) and US 5,652,192 (Matson et al.).
[0184] The content of tetragonal and / or cubic phases in zirconia grains can be adjusted by changing the amount of phase-stabilizing components added during the production process.
[0185] The starting sol is usually concentrated.
[0186] To obtain a more concentrated sol, at least a portion of the water-based medium is removed from the zirconium oxide-based sol.
[0187] According to one implementation, the zirconium oxide-based sol undergoes dialysis or filtration.
[0188] The content of crystalline nano-sized zirconium oxide particles in the concentrated starting sol is typically in the range of 20% to 70% by weight.
[0189] In some implementations, the zirconium oxide-based sol can undergo a solvent exchange process.
[0190] Organic liquids with boiling points higher than water can be added to the effluent. Examples of suitable organic liquids for solvent exchange methods include 1-methoxy-2-propanol, N-methylpyrrolidone, or diethylene glycol ethyl ether. Water can then be removed by methods such as distillation, rotary evaporation, or oven drying.
[0191] Zirconia-based sols contain zirconia-based particles dispersed and / or suspended (i.e., dispersed, suspended, or a combination thereof) in an aqueous / organic matrix.
[0192] Other components may be added to the starting sol: radiation-curable components, photoinitiators and optional organic dyes, inhibitors, soluble inorganic colorants and other additives (if required).
[0193] The preparation of printing sols is usually carried out under safe light conditions to avoid undesirable premature polymerization.
[0194] In another step, radiation-cured zirconia sol B x Apply to at least a portion of the outer surface of a zirconia gel product. Radiation-curable zirconia sol B x Also known as coating sol.
[0195] Radiation-cured zirconia sol B x The composition of [the substance] may be the same as or different from that of radiation-cured zirconia sol A in terms of chemical composition and / or physical properties.
[0196] If the composition is different, then radiation-cured zirconia sol B x The composition differs from that of radiation-cured zirconia sol A in the following characteristics, either individually or in combination:
[0197] a) The color or content of the coloring component;
[0198] b) Content of crystal phase stabilizer components;
[0199] c) Viscosity;
[0200] d) Weight percentage of crystalline zirconium oxide particles in the sol.
[0201] Combinations of a) and b), or a) and c), or b) and c), or b) and d) are sometimes preferred.
[0202] In some implementations, the viscosity difference between the sols is typically greater than a ratio of at least 1.2, 1.5, or 2.
[0203] The use of layer-by-layer manufacturing methods to process radiation-curable chemical compositions is well-known. This method is often referred to as 3D printing.
[0204] This method typically includes the following steps:
[0205] Provide a layer of structural material on the surface.
[0206] Radiation-cured structural material layers will be used to solidify the portions of the 3D product to be manufactured.
[0207] An additional layer of structural material is provided that is in contact with the radiation-cured surface of the preceding layer.
[0208] Repeat the above steps until a 3D product is obtained.
[0209] This method includes the step of applying radiation to the surface of a radiation-curable material, wherein the radiation is applied only to those portions of the surface that will subsequently form part of the article to be produced.
[0210] Radiation can be applied using, for example, a laser beam or through mask image projection. The use of mask image projection-based stereolithography (MIP-SL) is sometimes preferred because it allows for faster article manufacturing.
[0211] The MIP-SL method can be described as follows:
[0212] i. Provide a three-dimensional digital model of the product to be manufactured.
[0213] ii. The three-dimensional digital model consists of a set of horizontal slices.
[0214] iii. Each thin slice is converted into a two-dimensional mask image.
[0215] iv. The mask image is then projected onto the surface of the radiation-cured material located in the construction platform (e.g., having the shape of a barrel) using a radiation source.
[0216] v. Radiation-cured materials cure only in those exposed areas.
[0217] vi. A construction platform containing a radiation-curable material or a layer of cured material is moved relative to a radiation source, wherein a new layer of radiation-curable material is provided to come into contact with the layer of cured material produced in a previous step.
[0218] vii. Repeat steps (iv) to (vi) until the desired article is formed.
[0219] Projecting a mask image onto a radiation-curable material can be done from top to bottom or bottom to top relative to the orientation of the barrel.
[0220] Using a bottom-up approach may be beneficial because it requires less radiation-cured material.
[0221] The radiation-curable zirconia sol described in this text has been found to be particularly suitable for processing in mask image projection stereolithography methods using bottom-up projection techniques.
[0222] Further details of this processing step are described in US 4,575,330 (Hull), US 6,283,997 (Garg et al.), or US 8,003,040 B2 (El-Siblani).
[0223] The processing of radiation-curable zirconia sol can be accomplished by using the following parameters alone or in combination:
[0224] The thickness of the radiocurable zirconia sol exposed to radiation is 0.001 mm to 0.500 mm or 0.01 mm to 0.4 mm.
[0225] The energy dose per layer is 5 mJ / cm². 2 Up to 100mJ / cm 2 or 8mJ / cm 2 Up to 50 mJ / cm 2 Within the range.
[0226] Radiation-cured zirconia sol B x The application can be done manually or automatically using, for example, a robot.
[0227] Using automated systems can help increase throughput and promote the repeatability of the application steps.
[0228] For automation purposes, the use of, for example, gantry robot designs has been found to be appropriate. Radiation-cured zirconia sol B x It can be applied using mechanical tools such as brushes, spray nozzles, or by using an inkjet system. If necessary, radiation-cured zirconia sol B... xIt can be applied to the surface once or repeatedly.
[0229] Different radiation-curable zirconia sols B can be applied if needed. x (B1, B2, B3, B4, etc.)
[0230] Applying different radiation-cured zirconia sol B x This can help to further customize dental zirconia products, for example, in terms of color and / or translucency.
[0231] If needed, radiation-cured zirconia sol B x It can also be applied using top-down stereoscopic lighting techniques or volumetric layering manufacturing methods.
[0232] For example, a top-down continuous manufacturing apparatus as described in, for instance, US 2022 / 0380260 A1 (Shah et al.) can be used to produce a gel comprising a precise print from a first sol (e.g., printing sol A), a personalized shaped interface between two regions, and a 3D controlled coating of a second sol (e.g., coating sol B). x This method may include the following steps:
[0233] A first gel is generated with a predefined reference orientation, wherein the first gel is based on a first printable sol;
[0234] A second printable sol is placed in a manufacturing apparatus, which includes a printer barrel with top-down light projection and a lift for moving parts into the sol.
[0235] In the manufacturing apparatus, the first gel is processed with the coating area of the second sol not undercut by the first area. (That is, it can be cured by light projected from top to bottom.)
[0236] A second print is produced on top of the first print by advancing the first gel into a resin bath while projecting an appropriate light pattern to solidify the second printable sol into a gel.
[0237] The obtained multi-component gel can be processed into a fully dense ceramic using methods described elsewhere in this text.
[0238] Alternatively, volumetric stack fabrication systems can be used to construct multi-component gels. Volumetric methods offer the ability to print on non-planar surfaces, require minimal support, and produce smooth surfaces. Useful systems have been described by Toombs et al. (Science 376, April 15, 2022), Madrid Woolfe et al. (Adv. Sci. 2022, 9, 2105144), Reehly et al. (Nature 2020, Vol. 588, pp. 620–24), Huffman et al., Multiphoton Imaging Methods in a Scattering and / or Absorbing Medium, and article (US20220350127A1). This approach may include the following steps:
[0239] A first gel is produced with a predefined reference orientation, wherein the first gel is based on a first printable sol; the printer may have the above-described type, including a volumetric system.
[0240] The second printable sol is placed in a volumetric printer, and the first gel is arranged in a sol bath in the printer with a known orientation.
[0241] A second print is generated on the surface of the gel as the light source and the printer barrel move relative to each other and project an appropriate light pattern.
[0242] Alternatively, during printing, the sol composition in the volumetric printer is modified in a coordinated manner by allowing the dopant stream to flow into the bath while simultaneously projecting an appropriate light pattern into the barrel to reveal the desired recovery portion of the composition upon light exposure.
[0243] The multi-component gel can be processed into fully dense ceramic articles using methods described herein or known to those skilled in the art. Additional sols representing different properties can also be printed onto the article. Some additional properties include incomplete calcification, decalcification, cracking, various stains, etc. A particular advantage of the laminated manufacturing method is the ability to locally control the presence or absence of coatings on the printable surface. Furthermore, the coating thickness can be locally controlled from the voxel thickness level to the millimeter level. When carefully designed, articles coated from carefully selected sols can resemble natural dentin and enamel layers.
[0244] The curing of radiation-curable zirconia sol is usually carried out by radiation. The wavelength of the radiation is typically in the range of 300 nm to 500 nm or 365 nm to 460 nm.
[0245] According to one implementation scheme, the processing of radiation-curable zirconia sol A and zirconia sol B... xRadiation curing is carried out at different radiation wavelengths.
[0246] For example, the curing of radiation-curable zirconia sol A is carried out at wavelengths in the range of 365 nm to 420 nm, while radiation-curable zirconia sol B... x The curing is carried out at wavelengths in the range of 420 nm to 460 nm. Therefore, the wavelength used for curing radiation-curable zirconia sol A can be compared with that used for curing radiation-curable zirconia sol B. x It has a short wavelength.
[0247] In multiphoton printing, the wavelength is twice the wavelength required to activate the initiator. In Xolography, a single wavelength can be used to activate a second initiator.
[0248] The upconversion photopolymerization strategy (Sanders et al., Nature 2022 604 474-478) can also be used to allow printing at longer wavelengths, where light scattering caused by nanoparticles and interference from coloring ions are minimized.
[0249] The method described herein also includes the step of converting zirconia gel products into zirconia aerogel products.
[0250] Zirconia aerogel articles are formed by removing liquid from zirconia aerogel articles without excessive shrinkage (e.g., no more than about 30% or 40% by volume).
[0251] If water is present, it can be removed from the zirconia gel product via alcohol exchange to provide at least a partially dehydrated gel. The zirconia gel product is then transformed or converted into a zirconia aerogel product by removing alcohol (if present) from the partially dehydrated zirconia gel product via, for example, supercritical extraction.
[0252] Zirconia aerogel products can be characterized by the following characteristics, either alone or in combination:
[0253] (a) Contains crystalline zirconium oxide particles having an average primary particle size in the range of 2 nm to 50 nm, or 2 nm to 30 nm or 2 nm to 20 nm;
[0254] (b) Content of crystalline zirconium oxide particles: at least 40% by weight%
[0255] (c) It has an organic content of at least 3% by weight or in the range of 3% to 50% by weight;
[0256] (d) The lengths of two of the x, y, and z dimensions: at least 3 mm, or at least 5 mm, or at least 8 mm;
[0257] (e) Density: 0.5 g / cm³ 3Up to 1.5g / cm 3 .
[0258] Features (a) and (b), or (a), (b) and (c), or (b), (d) and (e) may be preferred.
[0259] If applied, the supercritical extraction step can be characterized by at least one, more, or all of the following characteristics:
[0260] (a) Temperature: 20°C to 100°C, or 30°C to 80°C, or 15°C to 150°C;
[0261] (b) Pressure: 5 MPa to 200 MPa, or 10 MPa to 100 MPa, or 1 MPa to 20 MPa, or 5 MPa to 15 MPa;
[0262] (c) Duration: 2h to 175h, or 5h to 25h, or 1h to 5h;
[0263] (d) Extraction or drying medium: carbon dioxide in its supercritical stage.
[0264] The combination of features (a), (b) and (d) is sometimes preferred.
[0265] Supercritical fluid extraction can remove all or most of the liquid from printed aerogel articles. In some embodiments, the aerogel contains some residual organic liquid. The residual liquid can be up to 6% by weight based on the total weight of the aerogel article. For example, the aerogel article may contain up to 5% by weight, up to 4% by weight, up to 3% by weight, up to 2% by weight, or up to 1% by weight of organic liquid.
[0266] The removal of the organic liquid results in the formation of pores within the dried structure. Preferably, the pores are large enough to allow gases from the decomposition products of the polymer material to escape without causing the structure to crack when the dried structure is further heated to burn off the organic material and form a sintered article.
[0267] In another step, the zirconia aerogel product is typically heat-treated.
[0268] Depending on the heat treatment conditions, heat treatment can produce calcined dental zirconia products, pre-sintered dental zirconia products, or sintered dental zirconia products.
[0269] Heat treatment can be performed in one or more steps, and can be performed at different physical locations if desired.
[0270] To obtain calcined dental zirconia products, a heating step is performed to remove organic residues remaining in the zirconia product before final sintering. Removing organic residues before sintering reduces the risk of breakage during sintering.
[0271] The heating process is typically carried out at temperatures below 800°C, 700°C, or 600°C. Typical temperature ranges are 400 to 800°C or 500 to 700°C.
[0272] The heating step typically involves the time required to burn off the organic components in the zirconia product. Typical time ranges are 5 to 100 hours or 10 to 50 hours.
[0273] To obtain pre-sintered dental zirconia products, the following conditions are typically applied, alone or in combination:
[0274] Temperature: 900°C to 1,100°C, or 950°C to 1,090°C, or 975°C to 1,080°C;
[0275] Atmosphere: Air or inert gas (e.g., nitrogen, argon);
[0276] Duration of stay: 0h to 24h or 0.1h to 5h;
[0277] Duration: Until the density of the sintered material reaches 40% to 60% of its original density.
[0278] Residence time (i.e., the time during which the aerogel article is held at that temperature) also helps to adjust strength and / or hardness according to specific needs, and can help facilitate the removal of support structures that may be generated during the lamination manufacturing steps.
[0279] To obtain sintered dental zirconia products, the following conditions are typically applied:
[0280] Temperature: 1,100°C to 1,400°C or 1,200°C to 1,350°C;
[0281] Atmosphere: Air or inert gas (e.g., nitrogen, argon);
[0282] Duration: Until the porosity of the zirconia product is less than 0.1% by volume or less than 0.05% by volume.
[0283] Duration of stay: 0.1h to 6h or 0.2h to 5h;
[0284] Pressure: 500 hPa to 1,500 hPa.
[0285] However, it is also possible to first provide pre-sintered dental zirconia products, which are then sintered later into sintered dental zirconia products.
[0286] During the heating step, the porous dental ceramic article is sintered into its final shape, thereby changing its size, density, hardness, flexural strength and / or grain size.
[0287] Heating temperature and residence time (i.e., the period of time during which a specific temperature is maintained) are usually related. Higher temperatures typically require only shorter residence times.
[0288] If necessary, the methods described in this text may include additional steps.
[0289] According to one implementation scheme, radiation-curable sol B x It is applied to the outer and inner surfaces of the zirconia gel product.
[0290] This implementation can help achieve a glossy surface on both sides of the dental article. Alternatively, a glossy surface can be obtained on the outer surface, while the inner surface retains a more matte finish.
[0291] According to one implementation scheme, at least two different radiation-curable sols B 1,2 Apply to portions of the outer and / or inner surfaces of zirconia gel products.
[0292] Different colored zirconia sols can be used to achieve different colored surfaces.
[0293] This allows for the provision of custom dental products tailored to the individual circumstances of a patient's mouth.
[0294] Apply a more opaque zirconia sol B to the inner surface of dental products. x It can help to mask the dark surface of a dental post without affecting the reflection depth on the outer surface of the dental product.
[0295] According to one embodiment, radiation-curable sol B1 is applied to a portion of the outer surface of the zirconia gel article, and radiation-curable sol B2 is applied to a portion of the inner surface of the zirconia gel article.
[0296] The methods described herein may also include the following steps, individually or in combination:
[0297] (a) Cleaning steps;
[0298] (b) Drying step;
[0299] (c) Post-curing step;
[0300] (d) Ion exchange steps;
[0301] (e) The step of removing the support structure (if present), for example, from the sintered zirconia ceramic article or at an earlier stage.
[0302] The combination of the following steps is sometimes preferred: (a) and (c); (a), (c) and (e); (a), (b), (c) and (e).
[0303] After processing radiation-curable zirconia sol A, the resulting zirconia gel product is typically removed from the apparatus used for the lamination manufacturing process.
[0304] If necessary, clean the surface of the zirconia gel product, for example by rinsing it with liquid or immersing it in liquid.
[0305] Suitable liquids preferably include mixtures thereof or the same liquids used in the sols described herein.
[0306] Suitable liquids include low-boiling alcohols (e.g., alcohols with boiling points below 100°C; such as methanol, ethanol, propanol) and mixtures thereof as described in this text, or high-boiling solvents as described in this text, preferably the same liquid present in the sol, such as diethylene glycol ethyl ether.
[0307] Alternatively, cleaning can consist of simply allowing uncured sol on the parts to settle to the desired level. This method can be facilitated by rotating the parts to allow centrifugal force to remove excess material, while presenting a smooth and generally glossy surface that typically cures in situ upon light exposure.
[0308] If necessary, a drying step may be performed to remove at least partially any organic liquid or water (if present) from the zirconia gel product.
[0309] This drying step typically occurs before the supercritical extraction step.
[0310] Drying is typically carried out under ambient conditions at temperatures ranging from 20 to 200°C.
[0311] If necessary, zirconia gel products can be post-cured by applying radiation or heat.
[0312] Such steps help to improve the stability of zirconia gel products by further increasing the degree of polymerization.
[0313] If present, the post-curing step can be characterized by the following features, either individually or in combination:
[0314] Apply radiation with wavelengths of 200nm to 500nm or 350nm to 460nm;
[0315] A heating step is employed, with the temperature below the temperature at which drying occurs or the temperature used for debinding or calcination; for example, 30°C to 110°C or 40°C to 80°C.
[0316] Typically in radiation-cured zirconia sol B x A post-curing step is performed after the radiation curing step.
[0317] Pre-sintered products can optionally be immersed in an alkaline solution, such as an aqueous solution of ammonium hydroxide. Because the products are porous at this stage of the process, immersion effectively removes undesirable ionic species such as sulfate ions.
[0318] After soaking, remove the product from the solution and wash it thoroughly with water. The product can be soaked in water for any desired period of time, such as at least 30 minutes, at least 1 hour, at least 2 hours, or at least 4 hours. If necessary, the soaking process can be repeated several times by replacing the water with fresh water.
[0319] After soaking, the articles are typically dried in an oven to remove water. For example, the articles can be dried by heating in an oven at a temperature set to at least 80°C, at least 90°C, or at least 100°C. For example, the temperature can be maintained for at least 30 minutes, at least 60 minutes, or at least 120 minutes in the range of 80°C to 150°C, 90°C to 150°C, or 90°C to 125°C.
[0320] Ion exchange steps can typically be characterized by the following characteristics, either alone or in combination: duration: 5 h to 24 h; medium: aqueous ammonium hydroxide solution (e.g., 1 N concentration); temperature: 20 °C to 25 °C.
[0321] Depending on the layered manufacturing method used, the resulting 3D printed article may include a support structure.
[0322] If present, these supporting structures need to be removed before dental products can be attached to the teeth in the patient's mouth.
[0323] The support structure can be removed at any suitable time during the method. The support structure can be removed after any of the following steps: post-curing step, step of converting zirconia gel product into zirconia aerogel product, ion exchange step, heat treatment step (e.g., calcination, pre-sintering or sintering step).
[0324] This removal can be done manually or through automated methods. Typically, a cutting tool is used.
[0325] The present invention also relates to dental articles that can be obtained or acquired by the methods described herein. Such dental articles have an outer surface and an inner surface.
[0326] Dental products can take the shape of crowns, bridges, inlays, high inlays, facets, brackets, buccal tubes, splints, or buttons.
[0327] Dental products can be pre-sintered dental zirconia products or sintered dental zirconia products.
[0328] Pre-sintered dental zirconia products can be characterized by the following characteristics, either individually or in combination:
[0329] Density: 2.5 g / cm³ 3 Up to 3.5g / cm 3 ;
[0330] Display the type IV N2 adsorption and desorption isotherms and hysteresis loops according to the IUPAC classification;
[0331] Showing type IV N2 adsorption and desorption isotherms with H1 type hysteresis loops according to IUPAC classification;
[0332] Type IV N2 adsorption and desorption isotherms with H1 type hysteresis loops according to IUPAC classification are shown in the p / p0 range of 0.70 to 0.99.
[0333] BET surface: 15m 2 / g to 100m 2 / g or 16m 2 / g to 60m 2 / g.
[0334] The material of pre-sintered dental zirconia products can be characterized by the following characteristics, either individually or in combination:
[0335] ZrO2 content: 70 mol% to 98 mol%
[0336] HfO2 content: 0 mol% to 2 mol%
[0337] Y2O3 content: 2 mol% to 8 mol%
[0338] Al2O3 content: 0 mol% to 0.5 mol%
[0339] Coloring component: 0 mol% to 1 mol%, comprising oxides selected from Fe, Mn, Er, Pr, Tb, Nd, Cr, Co, Mo, and mixtures thereof.
[0340] Mole % relative to pre-sintered dental zirconia products.
[0341] According to another embodiment, the pre-sintered dental zirconia article has a composition characterized by the following features:
[0342] ZrO2 content: 90 mol% to 98 mol%
[0343] HfO2 content: 0 mol% to 2 mol%
[0344] Y2O3 content: 3 mol% to 6 mol%
[0345] Al2O3 content: 0 mol% to 0.1 mol%.
[0346] Coloring component: 0.01 mol% to 0.5 mol%, comprising oxides selected from Fe, Mn, Er, Pr, Tb, Nd, Cr, Co, Mo, and mixtures thereof.
[0347] Mole % relative to pre-sintered dental zirconia products.
[0348] A higher Y₂O₃ content is found to typically lead to an increase in the cubic phase in zirconia ceramics after sintering to the final density. A higher cubic phase content may result in better translucency.
[0349] Dental products in the sintered state can be characterized by the following characteristics, either individually or in combination:
[0350] (a) The thickness between the outer and inner surfaces at at least one cross-section: 0.3 mm to 0.5 mm;
[0351] (b) Zirconia Sol B x Surface roughness of the applied surface area: less than 0.4µm;
[0352] (c) Zirconia sol B x Gloss level of the surface area to which the gloss has been applied: at least 50 GU, or in the range of 50 GU to 200 GU or 80 GU to 180 GU;
[0353] (d) Opalescence: at least 10.
[0354] Features (a) and (b), or (a) and (c), or (a), (b) and (d), or combinations of (a), (b) and (c) are sometimes preferred.
[0355] Depending on the chemical composition and associated crystal structure, greater than 5.80 g / cm³ 3 or greater than 5.90 g / cm³ 3 or greater than 6.00 g / cm 3 Or greater than 6.05 g / cm³ 3 The density indicates that a dental product is close to or has been fully sintered and is therefore essentially completely dense.
[0356] Dental products typically have a porosity of less than 0.1% by volume or less than 0.05% by volume.
[0357] Dental products exhibit excellent reflectivity or gloss, which essentially matches the reflectivity of natural tooth surfaces.
[0358] The method described herein allows for the manufacture of dental products with thin walls.
[0359] The opalescence of dental products is within the range that matches the opalescence of natural teeth.
[0360] Due to the radiation-curable zirconia sol B x It is applied to at least a portion of the outer surface of the zirconia gel article, so that the surface roughness of the dental article can be reduced to a level acceptable to the patient after the heat treatment step.
[0361] Surface roughness is typically <0.4µm, <0.3µm, or <0.2µm.
[0362] The volume of zirconia gel products is typically at least 1.1 times, or at least 1.2 times, or at least 1.3 times larger than that of zirconia aerogel products.
[0363] The volume of zirconia aerogel products is typically at least 2, 3, or 4 times larger than that of zirconia sintered products.
[0364] Therefore, the volume of the dental artifact decreases throughout the entire process. This also... Figure 1 As shown in the image.
[0365] The chemical composition of sintered zirconia products is essentially the same as that of pre-sintered zirconia products. The content of oxide components remains unchanged.
[0366] The following provides more specific implementation methods for the methods and dental products described in this text:
[0367] Implementation Plan 1
[0368] The method may include the following steps, essentially consist of the following steps, or consist of the following steps:
[0369] (a) Provides a radiation-curable zirconia sol A comprising nanoscale crystalline zirconia particles as described herein, a phase stabilizer component, a liquid, a radiation-curable component, a photoinitiator, an optional coloring component, and an optional inhibitor component, wherein the phase stabilizer component is contained within the crystalline zirconia particles, and the optional coloring component may be contained within the crystalline zirconia particles or exist as a separate component.
[0370] (b) Processing radiation-cured zirconia sol A, which serves as a structural material, in a laminated manufacturing method to obtain a 3D zirconia gel product.
[0371] (c) Optionally clean the surface of the 3D zirconia gel, particularly for the purpose of removing residues of unreacted sol.
[0372] (d) Radiation-cured zirconia sol B x Apply to at least a portion of the outer surface of the 3D zirconia gel article.
[0373] (e) Post-curing the 3D zirconia gel product (e.g., by heating or light curing) to a temperature in the range of 35°C to 80°C or by additional light curing, particularly for the purpose of increasing the stability of the zirconia gel product.
[0374] (f) Optionally, the 3D zirconia gel product is soaked in another liquid (e.g., diethylene glycol ethyl ether or ethanol).
[0375] (g) Preferably, the 3D zirconia gel product is converted into a 3D zirconia aerogel product by applying a supercritical drying step, particularly for the purpose of removing liquid.
[0376] (h) Heating the 3D zirconia aerogel product to a temperature in the range of 400°C to 800°C, especially for the purpose of removing residual organic components and further improving stability.
[0377] (i) Heating the 3D product from the aforementioned steps to a temperature in the range of 800°C to 1100°C, particularly for the purpose of producing a 3D pre-sintered body with a porous structure.
[0378] (j) Optionally, an ion exchange step may be performed.
[0379] (k) Apply a sintering step to obtain a 3D sintered zirconia ceramic product.
[0380] (l) If a support structure exists, the remaining support structure from the article of manufacture may be removed, wherein step (l) may be performed after any of steps I, (g), (i) or (k).
[0381] Implementation Plan 2
[0382] A dental ceramic zirconia article, particularly a dental ceramic zirconia article obtainable or acquired by the method described herein, is characterized by the following properties:
[0383] The thickness between the outer and inner surfaces at at least one cross-section: 0.5 mm to 0.3 mm.
[0384] Zirconia sol B x Surface roughness of the applied surface area: < 0.4µm
[0385] Gloss level: at least 50 GU
[0386] Opalescence: at least 10,
[0387] ZrO2 content: 90 mol% to 98 mol%
[0388] HfO2 content: 0 mol% to 2 mol%
[0389] Y2O3 content: 3 mol% to 6 mol%
[0390] Al2O3 content: 0 mol% to 0.1 mol%.
[0391] Mole % relative to dental ceramic zirconia products.
[0392] The methods described herein typically do not include the step of applying a glass window layer after the sintering step.
[0393] In particular, the dental zirconia articles described in this text are not coated with any material other than the material used to manufacture the dental zirconia articles. In this respect, dental zirconia articles can be considered as monolithic dental zirconia articles.
[0394] The radiation-curable zirconia sol described herein is typically stored in suitable packaging materials before use to avoid undesirable premature curing of the sol.
[0395] Suitable packaging materials include containers, bottles, tubes, utensils, or foil bags, typically with a volume ranging from 10 ml to 10,000 ml.
[0396] The dental zirconia products described herein are particularly useful for repairing damaged teeth in patients' mouths.
[0397] Missing teeth can be molars or anterior teeth, with restoration of anterior teeth sometimes being the preferred option.
[0398] Therefore, dental zirconia products are used to treat damaged teeth in a patient's mouth.
[0399] This method typically involves attaching the inner surface of a dental zirconia article to the surface of the tooth to be treated.
[0400] Fixation can be achieved by using dental cement (in combination with dental adhesive and / or dental primer, if needed).
[0401] Dental adhesives interact directly with the enamel or dentin surface of teeth. Dental adhesives are typically one-part compositions that are radiation-curable and contain an olefinically unsaturated component with an acidic moiety, an olefinically unsaturated component without an acidic moiety, water, sensitizers, reducing agents, and additives.
[0402] Examples of dental adhesives are described in US 2020 / 0069532 A1 (Thalacker et al.) and US 2017 / 0065495 A1 (Eckert et al.). Dental adhesives are also commercially available, such as those from 3M. ™ Scotchbond ™Universal or 3M ™ Scotchbond ™ Universal Plus (3M Oral Care).
[0403] Suitable dental primers are described in US 6,126,922 (Rozzi et al.) and WO 00 / 69393 A1 (3M). Dental primers are also commercially available, for example, from 3M. ™ Transbond ™ XT primer (3M OralCare).
[0404] Dental adhesives that can be added to kit boxes include, in particular, self-adhesive resin adhesives containing an acidic polymerizable component (e.g., a (meth)acrylate component having a phosphoric acid or carboxylic acid moiety), a polymerizable component without an acidic moiety, an initiator system, and fillers.
[0405] Suitable dental cements are also commercially available, such as RelyX. ™ Unicem 2, RelyX ™ Universal, RelyX ™ Veneer or RelyX ™ Luting Plus (3M Oral Care).
[0406] The entire disclosure of all patents, patent documents, and publications cited herein is incorporated by reference as if each were individually incorporated. Various modifications and alterations to the invention will be apparent to those skilled in the art without departing from the scope and spirit of the invention. The foregoing specifications, examples, and data provide a description of the manufacture and use of the compositions of the invention and the methods of the invention. The invention is not limited to the embodiments disclosed herein. Those skilled in the art will understand that many alternative embodiments of the invention can be prepared without departing from the spirit and scope of the invention.
[0407] Example
[0408] The following embodiments further illustrate the purpose and advantages of this disclosure, but the specific materials and quantities listed in these embodiments, as well as other conditions and details, should not be construed as unduly limiting this disclosure.
[0409] Unless otherwise stated, all parts and percentages are by weight, all water is deionized, and all molecular weights are weight-average. Furthermore, unless otherwise stated, all experiments were conducted under ambient conditions (23°C; 1,013 mbar below sea level).
[0410] method
[0411] Crystallization structure and size methods (XRD analysis)
[0412] Dry zirconia samples were hand-ground using an agate mortar and pestle. A large amount of sample was applied to a glass microscope slide to which a section of double-sided adhesive tape had been adhered using a scraper. The sample was pressed into the adhesive tape by forcing it against the tape with the scraper blade. Excess sample was removed by scraping the sample area with the edge of the scraper blade, leaving a thin layer of particles adhering to the adhesive. Any remaining loosely adhered material was removed by forcefully striking the hard surface of the microscope slide. Corundum (Linde 1.0µm alumina polishing powder, batch C062, UnionCarbide, Indianapolis, IN) was prepared in a similar manner and used for instrument broadening calibration of the X-ray diffractometer.
[0413] X-ray diffraction patterns were obtained using a Philips vertical diffractometer with a reflective geometry and copper K. a Radiation and scattered radiation were recorded using proportional detectors. The diffractometer was equipped with a variable incident beam slit, a fixed diffraction beam slit, and a graphite diffraction beam monochromator. Full-spectrum scans were recorded from 25° to 55° 2θ(2q) using steps of 0.04° and a dwell time of 8 seconds. An X-ray generator of 45 kV and 35 mA was used. Data for corundum standards were collected in three independent regions on several separate corundum substrates. Similarly, data were collected in three independent regions on thin-layer sample substrates.
[0414] The observed diffraction peaks were identified by comparison with reference diffraction patterns contained in the International Data Center for Diffraction (ICDD) Powder Diffraction Database (Collection 1-47, ICDD, Newton Square, PA, USA). The diffraction peaks of the samples were attributed to either the cubic / tetragonal (C / T) or monoclinic (M) form of zirconia. For zirconia-based particles, the (111) peak of the cubic phase and the (101) peak of the tetragonal phase cannot be separated, and therefore these phases are reported together. The amount of each zirconia form was evaluated on a relative basis, and the zirconia form with the strongest diffraction peak was designated as a relative intensity value of 100. The strongest lines of the remaining crystalline zirconia forms were scaled relative to this strongest line and given values between 1 and 100.
[0415] The peak width of the diffraction maxima observed due to corundum was measured by profile fitting. The relationship between the average width of the corundum peak and the position (2q) of the corundum peak was determined by fitting a polynomial to these data to produce a continuous function for evaluating the instrument width at any peak position within the corundum testing range. The peak width of the diffraction maxima observed due to zirconia was measured by profile fitting of the observed diffraction peaks. The following peak widths were evaluated based on the presence of the zirconia phase:
[0416] Cubic / Quadrilateral (C / T): (1 1 1)
[0417] Monoclinic (M): (-1 1 1) and (1 1 1)
[0418] Using K a1 and K a2 All measurements were performed using the Pearson VII peak shape model for the wavelength components and the linear background model. Peak widths were calculated as full width at half maximum (FWHM) in degrees. Graphical fitting was performed using the capabilities of the JADE diffraction software suite. Peak widths were evaluated for three independent datasets obtained for the same thin-layer sample substrate.
[0419] The sample peaks were corrected for instrument broadening by interpolating the instrument width values from the corundum instrument calibration, and the corrected peak widths were converted to radians. The primary crystal size was calculated using the Scherrer formula.
[0420] Crystallite size (D) = Kl / b (cos q)
[0421] In the Scherrer formula, K is the shape factor (0.9 here), l is the wavelength (1.540598 Å), b is the peak width (in radians) calculated after correction for instrument broadening, and q is equal to half the peak position (scattering angle). b equals [calculated peak FWHM - instrument width] (converted to radians), where FWHM is the full width at half maximum. The cubic / tetragonal (C / T) average crystallite size is measured as the average of three measurements using the (1 1 1) peak. That is,
[0422] C / T average crystallite size = [D(1 1 1)] 区域1 +D(1 1 1) 区域2 +D(1 1 1) 区域3 ] / 3.
[0423] Photon Correlation Spectroscopy (PCS) Method
[0424] Particle size measurements were performed using a light scattering particle size analyzer equipped with a red laser with a wavelength of 633 nm (trade name "ZETASIZER-Nano Series, Model ZEN3600", available from Malvern Instruments Inc., Westborough, MA). Each sample was analyzed in a 1 square centimeter polystyrene sample cuvette. Approximately 1 gram of deionized water was filled into the sample cuvette, followed by a few drops (approximately 0.1 gram) of zirconia-based sol. The composition in each sample cuvette was mixed by aspirating the composition (e.g., the sample) into a clean pipette and then returning the composition to the sample cuvette several times. The sample cuvettes were then placed in the instrument and equilibrated at 25°C. The instrument parameters were set as follows: dispersant refractive index 1.330, dispersant viscosity 0.8872 MPa-s, material refractive index 2.10, and material absorbance 0.10 units. An automatic size measurement program was then run. The instrument automatically adjusted the laser beam position and attenuator settings to obtain optimal particle size measurements.
[0425] The light scattering particle size analyzer illuminates a sample with a laser and analyzes the intensity fluctuations of light scattered from the particles at a 173-degree angle. The instrument uses photon correlation spectroscopy (PCS) to calculate particle size. PCS uses the fluctuating light intensity to measure the Brownian motion of particles in a liquid. The particle size is then calculated as the diameter of a sphere moving at the measured velocity.
[0426] The intensity of light scattered by a particle is proportional to the sixth power of the particle size. The Z-mean size, or cumulative average, is the average value calculated from the intensity distribution, based on the assumption that the particles are unimodal, monodisperse, and spherical. The correlation function calculated from fluctuating light intensity is the intensity distribution and its average value. The average value of the intensity distribution is calculated based on the assumption that the particles are spherical. The Z-mean size and the average value of the intensity distribution are more sensitive to larger particles than to smaller particles.
[0427] The volume distribution gives the percentage of the total particle volume corresponding to particles within a given size range. The volume-mean size is the particle size corresponding to the average of the volume distribution. Because the particle volume is proportional to the cube of its diameter, this distribution is less sensitive to larger particles than the Z-mean size. Therefore, the volume-mean size is typically a smaller value than the Z-mean size.
[0428] Methods for measuring oxide content
[0429] Oxide content was measured using a thermogravimetric analyzer (trade name "TGA Q500" from TA Instruments, NewCastle, DE, USA). The sample (approximately 50 mg) was loaded into the TGA and heated to 900°C in air. The oxide content of the sample was equal to its residual weight after heating to 900°C.
[0430] Methods for measuring Archimedes density
[0431] The density of the sintered material was measured using the Archimedes technique. Measurements were performed on a precision balance (labeled “XSE204”, from Mettler-Toledo, LLC, Columbus, OH, USA) using a density determination kit (labeled “DensityDetermination Kit for Excellence XP / XS Analytical Balances”, from Mettler-Toledo, LLC, Columbus, OH, USA). The sample was first weighed in air (A), then immersed in water and weighed (B). The water was distilled and deionized. Three drops of wetting agent (available under the trade name “PERVITRO 75%” from Mettler-Toledo, LLC, Columbus, OH, USA) were added to 250 ml of water. The density was calculated using the equilibrium density function, expressed as ρ = (A / (AB)) * (ρ0 - ρ L ) + ρ L Where ρ0 is the density of water, and ρ L It is the density of air (0.0012 g / cm³). 3 Relative density can be obtained from the theoretical density of the reference material (). ρt To calculate ρ rel =(ρ / ρ t )*100.
[0432] Methods for measuring the opacity of ceramic products
[0433] The opacity of the ceramic specimens was evaluated using the following procedure. After sintering, the printed ceramic test pieces were approximately 1 mm ± 0.03 mm thick × 13 mm × 13 mm. The parallel surfaces of the samples were polished to a surface finish of 15 micrometers using a diamond lapping film (668X Diamond Lapping Film PSA, 3M, St. Paul, MN) on a water-lubricated Beta polishing machine (Buehler, Lake Bluff, IL) operating at 100 rpm. The polished samples were measured in reflectance mode using a spectrophotometer (X-Rite Color i7, Grand Rapids, MI, USA). Translucency (T) was determined according to T = 1 - RB / RW, where RB is the reflectance of the ceramic sample on a black substrate, and RW is the reflectance of the same sample on a white substrate. Higher translucency values indicate greater light transmittance and lower opacity. Opacity (O) was determined according to O = 100 - T.
[0434] Surface texture analysis methods
[0435] Surface texture of the samples was measured using a Keyence VK-X210 laser confocal microscope from Keyence Corporation, Osaka, Japan. Similar locations on each sample were located and imaged at 10x and 50x magnification before scanning the surface texture with a scanning laser. Various numerical statistics, including Ra and average surface roughness, were generated using the included software, based on measurements averaged over 10 parallel horizontal lines, each 287 micrometers long, clustered around the center of the imaging area.
[0436] Methods for measuring viscosity
[0437] If desired, viscosity can be measured at 23°C and controlled shear rates using a Physica MCR 301 rheometer with plate / plate geometry (Anton Paar, Graz, Austria). The plate diameter is 15 mm, and the separation gap between the plates is 0.5 mm. Shear rates start from 1,000 s⁻¹. -1 It dropped to 0.001s -1 .
[0438] pH value measurement method
[0439] If necessary, pH can be determined as follows: Disperse 1.0 g of the component (e.g., filler) in 10 ml of deionized water and stir for about 5 min. Immerse a calibrated pH electrode in the suspension and measure the pH during stirring.
[0440] Methods for determining elemental composition
[0441] If desired, elemental composition can be determined by X-ray fluorescence spectrometry (XRF), for example using the ZSX Primus II from Rigaku, Japan. This method is particularly suitable for analyzing solids, such as zirconia ceramics or glass materials.
[0442] Methods for measuring N2 adsorption isotherms, BET surface area, pore volume, and average connecting pore diameter
[0443] Samples were analyzed on a Quantachrome Instruments AUTOSORB-1 BET analyzer (Boynton Beach, FL). Samples were weighed and percolated at 200°C for two days, followed by an N2 adsorption process. The number and distribution of measurement points were appropriate, e.g., 55 adsorption points and 20 desorption points, with p / p0 ranging from 1 x 10⁻⁶. 6 The value is then increased from 1 and returned to 0.05 to obtain the complete isotherm. Specific surface area S is calculated using the BET method (for details of the calculation, see Autosorb-1 Operating Manual Ver. 1.51 IV. Theory and Discussion; Quantachrome Instruments, Inc.). Total pore volume V... liq The average pore size (d) is derived from the amount of vapor adsorbed at a relative pressure close to one (p / p0 is closest to 1) by assuming that the pores are subsequently filled with liquid adsorbate (see Autosorb-1 Operating Manual Ver. 1.51 IV. Theory and Discussion; Quantachrome Instruments, Inc. for details of the calculation). The average pore size (d) is derived from the surface area (S) and the total pore volume (V). liq )calculate: .
[0444] Methods for measuring reflectance / gloss
[0445] The reflectance / gloss of a product surface can be determined using an instrument called a gloss meter, which measures gloss units (GU). Here, a gloss sample is run on a Rhopoint Novo-Curve gloss meter (Rhopoint Americas, Troy, MI), calibrated at 60 degrees using 93.7 GU and 0 GU standards. The measurement procedure for the sample is as follows: Clean the sample surface with isopropyl alcohol and dry it. Place the sample with the surface of interest on the aperture of the device. Cover it with a black container (in this case, a black plastic can) to eliminate ambient light. 60-degree specular reflection on the measuring device.
[0446] Methods for measuring opalescence
[0447] The article is considered opalescent if the calculated opalescence value OP meets the following conditions:
[0448] OP = [(ClEa T * - ClEa R *) 2 + (ClEb T * - CIEb R *) 2 ] 1 / 2 =At least 10, or 10 to 40, or 15 to 40,
[0449] in
[0450] -(CIEa T * - CIEa R *) represents the difference between the transmission mode and the reflection mode in the red-green coordinate a*, and
[0451] -(CIEb T * - CIEb R *) represents the difference between the transmission mode and the reflection mode in the yellow-V color coordinates b*.
[0452] The OP value can be determined using the above formula with a sample that is 1.0 mm high and 15 mm in diameter on a Color i7800 spherical benchtop spectrophotometer (x-rite, Michigan USA).
[0453]
[0454] Preparation method
[0455] Sol-based batch preparation
[0456] Zirconia-based sols, sol-I(a)–sol-V(a), were prepared as described in WO 2016 / 191534 A1 (Examples – Processing: Preparation of Sol-S1), except for the different feed compositions. The target compositions of sol-I(a)–sol-V(a) are listed in Table 1 below.
[0457]
[0458] The properties of sol-I(a)-sol-V(a) were determined using the methods described above. Table 2 below summarizes the crystallite sizes from XRD analysis, as well as PCS data, including volume-average size and Z-average size.
[0459]
[0460] Further processing of sol-I(a)-sol-V(a) is performed to increase its concentration and / or remove acetic acid (AcOH). One or a combination of ultrafiltration, percolation, and distillation is used. Percolation and ultrafiltration are performed using membrane filter cartridges (available under the trade name "M21S-100-01P" from Spectrum Laboratories Inc., Rancho Dominguez, CA). Distillation is performed using rotary evaporation.
[0461] Sol-I(b)-sol-V(b) based on diethylene glycol monoethyl ether was prepared from sol-I(a)-sol-V(a) by adding 2-[2-(2-methoxyethoxy)ethoxy]acetic acid (MEEAA) (3.5% to 7.2% by weight relative to the oxides in the sol) and an appropriate amount of diethylene glycol monoethyl ether (adjusted to the desired final oxide concentration in the sol, e.g., 55% by weight) and concentrating each sol by rotary evaporation. The weight percentages of oxides, acetic acid (AcOH), and 2-[2-(2-methoxyethoxy)ethoxy]acetic acid (MEEAA) obtained in each sol are given in Table 3.
[0462]
[0463] To prepare the precursor-sol SPr1, 13.34 g of sol-IV(b) and 9.56 g of sol-V(b) were placed in a vial and combined with 0.024 g of 2-[2-(2-methoxyethoxy)ethoxy]acetic acid (MEEAA), 1.30 g of acrylic acid, and 0.81 g of diethylene glycol monoethyl ether.
[0464] To prepare the precursor-sol SPr2, 1096.6 g of sol-I(b) was placed in a 1 L bottle and combined with acrylic acid (59.53 g) and diethylene glycol monoethyl ether (3.03 g).
[0465] To prepare the precursor-sol SPr3, 8.85 g of sol-III(b), 8.74 g of sol-IV(b) and 4.93 g of sol-V(b) were placed in vials and combined with acrylic acid (1.30 g) and diethylene glycol monoethyl ether (1.245 g).
[0466] To prepare the precursor-sol SPr4, 1303.4 g of sol-II(b) was placed in a 1 L bottle and combined with acrylic acid (77.66 g) and diethylene glycol monoethyl ether (125.75 g).
[0467] Sol-gel printing preparation
[0468] Preparation of printing sol PSO1
[0469] To prepare the printing sol PSO1, a portion of the precursor sol SPr2 (500 g) was placed in a 1-liter bottle and combined with diethylene glycol monoethyl ether (33.5 g), hydroxyethyl acrylate (HEA) (2.2 g), trimethylolpropane triacrylate (“SR351H”) (47.1 g), and two different polyurethane acrylates: CN975 (15.7 g) and CN9031 (7.8 g). Prior to printing, OMNIRAD 819 (0.1 wt% relative to the sol weight), butylated hydroxytoluene (BHT) (0.1 wt% relative to the sol weight), and indigo (0.05 wt% relative to the sol weight) were dissolved in the sol. The printing sol was then passed through a 1 μm filter.
[0470] Preparation of printing sol PSO2
[0471] To prepare the printing sol PSOl2, a portion of the precursor sol SPr4 (500 g) was placed in a 1-liter bottle and combined with diethylene glycol monoethyl ether (33.5 g), hydroxyethyl acrylate (HEA) (2.2 g), trimethylolpropane triacrylate (“SR351H”) (47.1 g), and two different polyurethane acrylates: CN975 (15.7 g) and CN9031 (7.8 g). Prior to printing, OMNIRAD 819 (0.1 wt% relative to the sol weight), butylated hydroxytoluene (BHT) (0.1 wt% relative to the sol weight), and indigo (0.05 wt% relative to the sol weight) were dissolved in the sol. The printing sol was then passed through a 1 μm filter.
[0472] Layer-by-layer 3D printing method
[0473] To 3D print an object from ceramic sol using layer-by-layer 3D printing, use the following procedure. Assemble the build tray with the fluoropolymer release film. Load approximately 50 mL of printing sol into the build tray at room temperature. Carefully prevent exposure by performing the procedure in a UV-filtered chamber (yellow lamp) or under low-light conditions when UV filtering is unavailable. Sand the build platform with sandpaper and clean it with IPA as needed. Load the STL file into the software and apply the support structure as needed. The printing settings for the ASIGA MAX-X43 UV stereolithography printer (from Asiga, Sydney, Australia) are listed in Table 4 below.
[0474]
[0475] Immediately after construction, the gel sample was removed from the construction platform and immersed in two used diethylene glycol monoethyl ether solvent baths, followed by immersion in a fresh solvent bath. Sol coating was then optionally performed as described in the sol coating method. The part was then placed in a Clearstone Technologies CA3200 inert UV curing chamber for post-curing, followed by 1 minute of 385nm LED exposure at 20% power under active nitrogen purging. It was then placed in a sealed container until the next step.
[0476] Methods for laminate manufacturing
[0477] Shah et al. (US 2022 / 0380260 A1) described an alternative method for laminate fabrication that can be used to create a gel from sol A or a surface layer from sol B. A layer of sol B is applied to the gel of sol A by placing sol B in a slot in a printer. The gel composed of sol A is then raised or lowered into a bucket or resin while an appropriate light pattern is projected onto the bucket to cure the desired sol B layer onto the gel A. The gel containing the surfaces of sol A and sol B is then removed from the printer.
[0478] Method for volumetric laminate manufacturing
[0479] If desired, methods for fabricating volumetric stacks, such as those described in Toombs et al. (Science 376, April 15, 2022), MadridWoolfe et al. (Adv.Sci.2022, 9, 2105144), Reehly et al. (Nature 2020, Vol. 588, pp. 620-24), and Huffman et al., Multiphoton Imaging Methods in a Scattering and / or Absorbing Medium, and the article (US20220350127A1), can also be used. The initiator level and exposure are adjusted to provide the components of sol A. The fabrication assembly of sol A is placed in a printer, and then the printer is filled with sol B. A light projection pattern of sol B volume rendering onto the surface of the sol A assembly is projected. The gel containing the surfaces of sol A and sol B is then removed from the printer.
[0480] Sol coating method
[0481] After printing and washing, but before the post-curing step as described in the layer-by-layer 3D printing method, optionally coat the sample with a printing sol or a modified precursor sol. When using a precursor sol, add 0.1% by weight of OMNIRAD 819. For coating, place the sample on a double-layered paper towel with the surface to be coated facing upwards. Load the sol into a 3 mL plastic pipette and repeatedly drop it onto the center of the sample until the entire surface is visibly wetted. Allow any excess sol to drip off the surface. Then, carefully lift the sample from the bottom using a depressor and move it to another paper towel. Let the sample sit for approximately 1 minute to allow any excess sol to be absorbed from the edges. Then continue with post-curing as described in the layer-by-layer 3D printing method. If coating both sides of the sample, coat the second side after post-curing as described herein, followed by an additional post-curing step.
[0482] Supercritical fluid extraction method
[0483] The printed gel was dried by supercritical fluid extraction, as described in the supercritical gel extraction method in the Examples section of WO 2016 / 191534 A1 (Mayr et al.).
[0484] Burn-out and pre-sintering methods
[0485] The dried gel was placed on a bed of zirconia beads in an alumina crucible. The crucible was covered with an alumina plate and then fired in air according to the following procedure:
[0486] 1-Heat from 20°C to 220°C at a rate of 18°C / hour.
[0487] 2- Heating from 220°C to 244°C at a rate of 1°C / hour.
[0488] 3-Heat from 244°C to 400°C at a rate of 6°C / hour.
[0489] 4- Heating from 400°C to 1,020°C at a rate of 60°C / hour.
[0490] 5- Cool from 1,020°C to 20°C at a rate of 120°C / hour.
[0491] Ion exchange methods
[0492] The pre-sintered body was placed in a 118ml glass jar containing approximately 2.5cm of 1.0N NH4OH and soaked for at least 16 hours. The NH4OH was then poured out, and the jar was filled with distilled water. The body was soaked in the distilled water for 1 hour. The water was then replaced with fresh distilled water. This process was repeated until the pH of the soaking water was equal to that of the fresh distilled water. The body was then dried at 90°C to 125°C for at least 15 minutes.
[0493] Sintering method
[0494] The pre-sintered ion exchanger was placed on a bed of zirconia beads in an alumina crucible. The crucible was covered with an alumina plate, and the sample was sintered in air according to the following procedure:
[0495] 1- Heating from 20°C to 1,020°C at a rate of 500°C / hour.
[0496] 2- Heating from 1,020°C to 1,225°C at a rate of 120°C / hour.
[0497] 3. Keep at 1,225°C for 2 hours.
[0498] 4- Cool from 1,225°C to 20°C at a rate of 500°C / hour.
[0499] Examples 1 to 4
[0500] Ceramic test pieces were printed using a layer-by-layer 3D printing method. At least some portions from each printed instance had a coating applied using a sol-coating method prior to the post-curing step. Uncoated samples from each printed instance were included for comparison. All samples were dried using a supercritical fluid extraction method, followed by treatment using burn-off and pre-sintering methods, ion exchange methods, and sintering methods to form fully dense ceramic articles.
[0501] Example 1 (Ex 1)
[0502] Example 1 demonstrates prototype panels printed using printing sol-PSol1, some of which have individual small pieces coated with the precursor-sol-SPr1 on the front or lip side. The coated panels exhibit increased smoothness and glossy light reflection. Figure 2 As shown in the two samples on the right, the coating remains smooth on the surface of the coated panel, while Figure 2 The two samples on the left show the uncoated samples.
[0503] Example 2 (Ex 2)
[0504] Example 2 demonstrates prototype panels printed with printing sol PSol1, where all individual pieces are coated with different precursor sols on both the front and back sides. All coated panels have precursor sol SPr2 on the front side and either SPr1 or SPr3 on the back side. SPr1 and SPr3 have different levels of masking dopants, resulting in subtle color differences between samples. The coated panels exhibit increased smoothness and glossy light reflection. The coating is consistently smooth across the entire surface of the coated panels.
[0505] Example 3 (Ex 3)
[0506] Example 3 demonstrates prototype panels printed with printing sol PSol2, some of which have their front or lip sides coated. In the coated parts, half are coated with precursor sol SPr1, while the other half are coated with the same sol (PSol2) used for printing the panels themselves. The coated panels exhibit increased smoothness and glossy light reflection. The coating is consistently smooth across the entire surface of the coated panels. Comparing samples with different sol coatings, those coated with precursor sol appear more uniformly smooth, while those coated with printing sol show some rougher patches. However, they are still smoother than the uncoated samples from the same group.
[0507] Three facets with the same shape (one uncoated, one coated with precursor sol, and one coated with printing sol) were selected for surface texture analysis. The results and comparisons can be found in the Surface Texture Analysis section.
[0508] Example 4 (Ex 4)
[0509] Example 4 demonstrates a prototype panel printed with printing sol PSO12, where some individual small pieces are coated on both the front and back sides with the same sol as the printing: PSO12. The coated panel exhibits increased smoothness and glossy light reflection. The coating is consistently smooth across the entire surface of the coated panel.
[0510] Comparative Example 1 (CE1)
[0511] Comparative Example 1 consists of a set of inlays printed with PSO2 without a coating in the printed state. The inlays were sintered and then delivered to a professional dental technician. The samples underwent conventional staining and glazing to produce a smooth surface and multiple colors on the lip surface of the inlays. The surface texture of one of the inlays having a shape matching that of the three from Example 3 was analyzed, as detailed in the Surface Texture Analysis section.
[0512] Surface texture analysis
[0513] Four faceted samples were analyzed using laser confocal microscopy to compare surface texture and roughness based on different surface treatment techniques. The analytical methods are detailed in the Surface Texture Analysis Methods section, and the results are described in Table 5.
[0514]
[0515] Examples and Analysis of Gloss Measurement
[0516] The gloss measurement samples were flat squares, 14mm x 14mm and 1.4mm thick. They were printed with printing sol PSO1, like the other panelized samples (Examples 1 to 4), and coated with the same PSO1 on one side. The coated side showed increased smoothness and glossy light reflection. Gloss measurements showed that the gloss of the coated side was significantly increased compared to the uncoated side. Full results are shown in Table 6.
[0517]
Claims
1. A method of producing a dental zirconia article, the method comprising the steps of: (a) working a radiation-curable zirconia sol A as a build material in a layer- by-layer manufacturing method comprising a radiation curing step to obtain a zirconia gel article having the shape of a dental article with an outer surface and an inner surface, (b) applying a radiation-curable zirconia sol B x on at least a portion of the outer surface of the zirconia gel article, (c) radiation curing of the radiation-curable zirconia sol B of step (b) x , (d) converting the zirconia gel article into a zirconia aerogel article, The radiation-curable zirconia sol A is different from the radiation-curable zirconia sol B in terms of chemical composition and / or physical properties x identical or different.
2. The method according to any one of the preceding claims, the radiation-curable zirconia sol A and the radiation-curable zirconia sol B x each comprising: crystalline zirconia particles, a crystalline phase stabilizer component, a radiation-curable component, a photoinitiator, a liquid, and an optional coloring component, an optional inhibitor component, wherein the crystalline phase stabilizer component is comprised in the crystalline zirconia particles and the optional coloring component can be comprised in the crystalline zirconia particles or present as a separate component.
3. The method according to any of the preceding claims, the radiation-curable zirconia sol A and / or the radiation-curable zirconia sol B x characterized by the following features, alone or in combination: viscosity: less than 500 mPa*s at 23 °C; showing a transmittance of at least 5% at a wavelength of 420 nm for a path length of 10 mm; pH value: 1 to 6.
4. The method according to any one of the preceding claims, the radiation-curable zirconia sol A and the radiation-curable zirconia sol B x differ in the following features alone or in combination: color or content of the coloring component; content of the crystalline phase stabilizer component; content of the crystalline zirconia particles; viscosity.
5. The method according to any of the preceding claims, the processing of the radiation- curable zirconia sol A and the radiation curing of the radiation-curable zirconia sol B x are carried out at different radiation wavelengths.
6. The method according to any one of the preceding claims, the converting step (d) comprising a supercritical extraction step.
7. The method according to any one of the preceding claims, the applying of the radiation- curable sol B x is carried out on portions of the outer surface and the inner surface of the zirconium oxide gel article.
8. The method according to any of the preceding claims, wherein in step (b) at least two different radiation-curable sols B are applied x .
9. The method according to any of the preceding claims, wherein the radiation- curable zirconia sol B x is applied by any of the following methods: manual coating method; top-down projection layer-by-layer manufacturing method; volume layer-by-layer manufacturing method.
10. The method according to any one of the preceding claims, wherein in step (b) a radiation-curable sol Bl is applied to the outer surface of the zirconia gel article, and a radiation-curable sol B2 is applied to the inner surface of the zirconia article, wherein the radiation-curable sol B2 differs from the radiation-curable sol Bl in the color or content of the coloring component, content of the stabilizer component, content of the crystalline zirconia particles, viscosity.
11. The method according to any one of the preceding claims, the method additionally comprising the step of heat treating the zirconia aerogel article to obtain a calcined dental zirconia article, a presintered dental zirconia article or a sintered dental zirconia article.
12. The method according to any one of the preceding claims, in particular the method comprising the steps of: (a) providing a radiation-curable zirconia sol A comprising nanoscale crystalline zirconia particles, a crystalline phase stabilizer component, a liquid, a radiation-curable component, a photoinitiator, an optional coloring component and an optional inhibitor component, as described in any one of the preceding claims, (b) working the radiation-curable zirconia sol A as a build material in a layer- by-layer manufacturing method to obtain a 3-dimensional zirconia gel article having an outer surface and an inner surface, (c) optionally cleaning the surfaces of the 3-dimensional zirconia gel, (e) post-curing the 3-dimensional zirconia gel article at a temperature in the range of 35 °C to 80 °C or by additional photocuring, (d) applying a radiation-curable zirconia sol B x on at least a portion of the outer surface of the 3-dimensional zirconia gel article, (f) optionally soaking the 3-dimensional zirconia gel article with another liquid, (g) converting the 3-dimensional zirconia gel article into a 3-dimensional zirconia aerogel article, (h) heating the 3-dimensional zirconia aerogel article to a temperature in the range of 400°C to 800°C, (i) heating the 3-dimensional article of the previous step to a temperature in the range of 800°C to 1100°C, (j) optionally performing an ion exchange step, (k) applying a sintering step to obtain a 3-dimensional sintered zirconia ceramic article, (l) optionally removing the support structure remaining from the support structure of step (b) from the article, if present, wherein step (l) can be performed after any one of steps (e), (g), (i) or (k).
13. A dental ceramic zirconia article having an outer surface and an inner surface, obtainable or obtained by the method of any one of the preceding claims.
14. The dental ceramic zirconia article having an outer surface and an inner surface according to the preceding claim, characterized by the combination of the following features: thickness between the outer surface and the inner surface at at least one cross section: 0.5 mm to 0.3 mm; Zirconium oxide sol B x Surface roughness of the surface area to which it has been applied: < 0.4 µm; gloss: at least 50 GU; opalescence: at least 10.
15. The dental ceramic zirconia article according to any one of claims 13 to 14, having the shape of a crown, a bridge, an inlay, an onlay, a veneer, a bracket, a buccal tube, a splint or a button.
Citation Information
Patent Citations
Additive manufacturing process for producing ceramic articles using a sol containing nano-sized particles
US10759707B2
Coloring solution for zirconia ceramics
US20150223917A1
Adhesive bonding composition and use thereof
US20170065495A1
Dental adhesive composition, preparation and use thereof
US20200069532A1
Multiphoton Imaging Methods in a Scattering and / or Absorbing Medium, and Articles
US20220350127A1